Study Of the Effect of Ship Ballast Water on Microorganisms and Organisms in The Port of Amurang - Ansar, Azhar Ariansyah; Wijaya, Haryadi; J.H. Rengga, Capt. Joseph; G. A. Rakka, Stevian (Jurnal Ilmiah PLATAX, 2025)
Ships are one of the most important modes of sea transportation for cargo and logistics. One vital system on board is the ballast water system, which functions to maintain the ship’s stability and balance during navigation. However, ballasting and deballasting activities can cause serious marine pollution due to the transfer of microorganisms and foreign aquatic species from one region to another. This process disrupts local ecosystems, poses health risks, and affects the coastal economy. Therefore, it is essential to manage ballast water in accordance with the D2 standard of the International Maritime Organization (IMO) Ballast Water Management Convention This research was conducted at Amurang Port using the TB. Raymond I vessel to determine the effectiveness of the heating treatment method for ballast water at temperatures above 75°C in reducing the number of microorganisms to meet the D2 standard. Sampling was carried out four times: seawater near the vessel, ballast water before treatment, ballast water after treatment, and seawater near the dock. Laboratory analyses were performed at the Manado Standardization and Industrial Services Center (BSPJI Manado). The results showed that heating ballast water above 75°C effectively reduced the number of microorganisms from 7.1 × 10³ CFU/mL before treatment to <1.0 × 10¹ CFU/mL after treatment, with Coliform levels <1.8 MPN/100 mL, meeting both the IMO D2 standard and the Indonesian Government Regulation No. 22 of 2021 on seawater quality standards. Thus, the heating treatment method is proven to be effective in minimizing marine pollution caused by ballast water discharge and in supporting the preservation of marine ecosystems at Amurang Port. Keywords: Ballast Water, Ballast Water Treatment, Microorganisms, IMO, Amurang Port, Heating Method.